ANALISIS PEMEROLEHAN BAHASA PADA ANAK USIA 4 TAHUN BERDOMISILI DI KOTA KARAWANG - Hani Handayani; Hendra Setiawan (Jurnal Membaca Bahasa dan Sastra Indonesia, 2022)
AbstractThis study intends or aims to explain or describe the language acquisition of children at the age of 4 years. This language barrier is seen from the aspect of daily life with the vocabulary that the 4 year old child has, without any help from others. This study uses a qualitative descriptive method, because it is taken from factual data from everyday life. The data were taken from the technique of observing and interviewing the child. And generated or issued with the vocabulary as it is. The researcher took research data from the child, namely the aspect of the child's vocabulary or seen from the syntactic language. From the data above, it can be concluded that the language or language acquisition of children at the age of 4 years can be obtained as is without any engineering or artificiality from the parents or the researcher himself.Keywords: Language acquisition, Vocabulary, Toddler